1992
DOI: 10.1097/00006254-199205000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Pregnancy-Screening and Neonatal-Immunization Program for Hepatitis B in Hamilton, Ontario, Canada, 1977–1988

Abstract: Blood Transfusion Service screened 98,712 pregnant patients for hepatitis B surface antigen (HBsAg) and identified 120 positives (0.12%). The number of positives ranged from six to 16 per year. We were able to trace and enroll 65 mothers (54%) and 96 of their children in the follow-up study. The majority of the women were between 20 and 30 years of age (95.4%) and married (86%), and about one-half were employed outside the home. Sixty-five percent were white and 34% Asian, and 20 countries were listed as their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…This is far higher than previous evaluations which reported three-dose vaccine coverage to be 59% in New York City 8 and 63% in Louisiana 9 and Ontario. 10 It is interesting to note that previous research in the mid-1980s from Alberta reported that 94% of infants born to carrier mothers had received appropriate vaccination, suggesting that the provincial prenatal screening and HBV prophylaxis program have consistently high uptake. 11 Despite this suc-cess, improvements can be made to ensure that all children are appropriately vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…This is far higher than previous evaluations which reported three-dose vaccine coverage to be 59% in New York City 8 and 63% in Louisiana 9 and Ontario. 10 It is interesting to note that previous research in the mid-1980s from Alberta reported that 94% of infants born to carrier mothers had received appropriate vaccination, suggesting that the provincial prenatal screening and HBV prophylaxis program have consistently high uptake. 11 Despite this suc-cess, improvements can be made to ensure that all children are appropriately vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…12 In two reports in China, these rates were reported as 7.2% and 13.7%. 13,14 Another study by Zhu in China found that 14.7% of these children carried HBsAg. 15 These evidence shows that vertical transmission of HBV infection is a serious health concern among societies, and those infected with the virus via this route must be under close clinical surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Active immunization with HB vaccine produces an HBsAg antibody response after a complete course in a high percentage of nonimmunocompromised recipients and it is hoped will lead to long-lasting protection [11]. The combinatio n of passive and active immunoprophylaxis in order to prevent HBV infection should only be considered in newborn infants of mothers who are HBsAg carriers [13][14][15][16]. The study confirmed that both schedtfles are effective in preventing symptomatic HBV infection after accidental exposure to HBsAg-positive blood.…”
Section: Discussionmentioning
confidence: 99%